2016
DOI: 10.1002/jnr.23949
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal H1N1 infection at E16 on FMRP, glutamate, GABA, and reelin signaling systems in developing murine cerebellum

Abstract: Prenatal viral infection has been identified as a potential risk factor for the development of neurodevelopmental disorders such as schizophrenia and autism. Additionally, dysfunction in gamma-aminobutyric acid (GABA), Reelin, fragile X mental retardation protein (FMRP)-metabotropic glutamate receptor 5 (mGluR5) signaling systems has also been demonstrated in these two disorders. In the current report, we have characterized the developmental profiles of selected markers for these systems in cerebella of mice b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 108 publications
(300 reference statements)
1
14
0
Order By: Relevance
“…We and others have shown that exposure to prenatal inflammation results in significant injury to the fetal brain including loss of pro-oligodendrocytes, a significant alteration in neuronal development, post-natal changes in gene expression as well as altered behavior [ 1 4 , 13 15 ]. Others have shown that systemic inflammatory stimuli such as viral infections or simply prenatal exposure to the viral mimetic poly I:C causes altered brain structure, neurochemical changes and behavioral deficits in offspring [ 5 , 16 19 ]. Despite this body of work demonstrating an association between prenatal inflammation and adverse neurological outcomes, the mechanism by which prenatal inflammation negatively impacts the developing brain is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown that exposure to prenatal inflammation results in significant injury to the fetal brain including loss of pro-oligodendrocytes, a significant alteration in neuronal development, post-natal changes in gene expression as well as altered behavior [ 1 4 , 13 15 ]. Others have shown that systemic inflammatory stimuli such as viral infections or simply prenatal exposure to the viral mimetic poly I:C causes altered brain structure, neurochemical changes and behavioral deficits in offspring [ 5 , 16 19 ]. Despite this body of work demonstrating an association between prenatal inflammation and adverse neurological outcomes, the mechanism by which prenatal inflammation negatively impacts the developing brain is not well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies have suggested that maternal immune activation (MIA) is linked to the development of SCZ ( Ghiani et al, 2011 ; Harvey and Boksa, 2012 ; Nouel et al, 2012 ; Ratnayake et al, 2012 ; Giother with the Viravanoli et al, 2014 ; Fatemi et al, 2017 ; Conway and Brown, 2019 ; Aguilar-Valles et al, 2020 ). Exposure to prenatal infection in critical stages of gestation is an environmental risk factor for the development of this neuropsychiatric disorder and can lead to alterations in GABAergic and glutamatergic signaling systems as well as RELN and inflammatory mediators.…”
Section: Resultsmentioning
confidence: 99%
“…We selected and analyzed five proteomes belonging to infectious agents that have been reported as related to or concomitant with ASD. That is, BDV [38][39][40] , RUBV [41][42][43][44][45][46] , MeV [41,47,48] , Influenza A virus [49][50][51] , MuV [41] . As a control, we used Parvovirus B19.…”
Section: Resultsmentioning
confidence: 99%
“…We pursued the hypothesis that peptide commonality between microbial and human proteins might have the potential to trigger cross-reactions in the human host during infection, thus inducing autoimmune pathologic sequelae [30][31][32][33][34][35][36][37] . Here, we test such a hypothesis by analyzing viral pathogens that have been related to ASD [38][39][40][41][42][43][44][45][46][47][48][49][50][51] -namely Borna disease virus, Rubella virus, Measles virus, Influenza A virus, and Mumps virus-and searching for amino acid (aa) sequences common to (i) human proteins that, when altered, have been associated with autistic disorders, and (ii) proteins expressed by Y-linked genes.…”
Section: Introductionmentioning
confidence: 99%